Survey on restoration on endodontically treated anterior teeth in Eastern region of Nepal: A questionnaire-based study - Singh, Amit Kumar; Mehta, Pawan (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: The preservation of natural tooth structure is the goal of endodontic and restorative dentistry. The optimal method for restoring teeth after root canal therapy is, however, still under debate for a very long time. Therefore, this study was conducted to detect the frequency of preferred methods of restoring endodontically treated teeth under different conditions. Methods: A structured questionnaire was distributed among general practitioners of the Eastern region of Nepal to find out the frequency of the best suitable material and method regarding restoration of endodontically treated teeth. The questionnaires were sent by electronic mail and out of 180 individuals, 92 responded. The respondents were asked to choose their favourite technique for restoring those teeth. One-way frequency tables were generated to summarize the responses. Two-way cross-tabulation tables were computed to show the relationship between the variables. Results: The majority of the respondents 42(45.70%), preferred to restore the tooth only with a tooth-color restorative material under condition A (>50% of tooth structure remaining). Under condition B (50% of tooth structure remaining), the majority of respondents 48(52.20%), preferred to use tooth-coloured crown and prefabricated post and tooth-coloured restoration 21(22.80%). Whereas, in condition C (